Research on Financial Investment Risk in Enterprise Financial Management - Yan, Jiyao; Zhang, Hao (IC-ITECHS, 2024)
This paper focuses on the financial investment risk in the financial management of enterprises, analyzes its causes, types and potential threats to the financial security of enterprises. It is pointed out that the main causes of financial investment risk are the lack of perfect risk management system, the insufficient ability of financial managers and the change of external environment. To deal with these risks, this paper puts forward a series of strategies, including building a comprehensive financial risk investment system, improving the professional quality of financial management team, balancing returns and risks, and strengthening internal control. The effectiveness of the proposed strategy is verified by case analysis. The research results of this paper not only enrich the theoretical system of financial investment risk management, but also provide practical guidance for enterprises, which is helpful to improve the level of financial security of enterprises and ensure steady development.